Penerapan Metode Imla’ Dengan Buku Hayya Nata’allamu Imla’ Untuk Meningkatkan Penguasaan Maharah Kitabah Santri Kelas VIII Program Tahfidz SMP PPTQ Al Asy’ariyyah Kalibeber Wonosobo Tahun Ajaran 2022/2023 - Muchammad Abdul Qodir Al Judiyyi; Robingun Suyud El Syam; Ali Imron (Pusat Riset dan Inovasi Nasional, 2024)
For pupils, education is a lifelong process that ends when they develop into adults. Arabic language classes, which cover hearing, speaking, reading, and writing, are offered at religious education institutions ranging from elementary schools to universities. For pupils in class 2 of the PPTQ Al-Asy'ariyyah junior high school Tahfidz program, Kalibeber Wonosobo, the author restricts the issue of adopting and refining maharah kitabah learning utilizing the Imla' technique with the book Hayya Nata'allamu imla'. Unlike trials where the researcher is the primary instrument, this research uses it to investigate the circumstances of natural objects. Two methodologies were used in the research: experiments using both qualitative and quantitative methods.